Synergistic Bimetallic Catalysis for Carboboration of Unsaturated Hydrocarbons - Rivera-Chao, Eva; Fra, Laura; Fañanás-Mastral, Martín (Synthesis, 2018)
Synergistic bimetallic catalysis has become a very efficient tool for the selective carboboration of unsaturated hydrocarbons. This synthetic approach is based on the use of a catalytically generated boron-substituted organocopper nucleophile in a cross-coupling reaction catalyzed by a second transition metal. This way, hydrocarbons can be used as pro-nucleophiles in this type of transformations thus rendering a clean and operationally simple alternative to the traditional cross-coupling methodologies. This review provides a summary of the developments on this topic and discusses both the synthetic utility and mechanisms of these reactions.1 Introduction2 Carboboration of Alkenes via Synergistic Catalysis3 Carboboration of 1,3-Dienes via Synergistic Catalysis4 Carboboration of Alkynes via Synergistic Catalysis5 Conclusions
Keywords: boron; copper; cross-coupling; synergistic catalysis; unsaturated hydrocarbons; palladium; C–C bond formation; C–B bond formation